Structural assembly of the PAS domain drives the catalytic activation of metazoan PASK - Sajina Dhungel; Michael Xiao; Rajesh Rajaian Pushpabai; Chintan K. Kikani (Proceedings of the National Academy of Sciences, 2025)
PAS domains are ubiquitous sensory modules that transduce environmental signals into cellular responses through tandem PAS folds and PAS-associated C-terminal (PAC) motifs. While this conserved architecture underpins their regulatory roles, here we uncover a structural divergence in the metazoan PAS domain–regulated kinase (PASK). By integrating evolutionary-scale domain mapping with deep learning-based structural models, we identified two PAS domains in PASK, namely PAS-B and PAS-C, in addition to the previously known PAS-A domain. Unlike canonical PAS domains, the PAS fold and PAC motif in the PAS-C domain are spatially segregated by an unstructured linker, yet a functional PAS module is assembled through intramolecular interactions. We demonstrate that this assembly is nutrient responsive and serves to remodel the quaternary structure of PASK that positions the PAS-A domain near the kinase activation loop. This nutrient-sensitive spatial arrangement stabilizes the activation loop, enabling catalytic activation of PASK. These findings revealed an alternative mode of regulatory control in PAS sensory proteins, where the structural assembly of PAS domains links environmental sensing to enzymatic activity. By demonstrating that PAS domains integrate signals through dynamic structural rearrangements, this study broadens the understanding of their functional and regulatory roles and highlights potential opportunities for targeting PAS domain–mediated pathways in therapeutic applications.